Turbo equalization with cancelation of nonlinear distortion for CP-assisted and zero-padded MC-CDM schemes - Dinis, Rui (2012)
In this paper, we consider MC-CDM schemes (MultiCarrier Code Division Multiplexing) where clipping techniques are employed to reduce the envelope fluctuations of the transmitted signals. Both CP-assisted (Cyclic Prefix) and ZP (Zero- Padded) MC-CDM schemes are studied. We develop frequencydomain turbo equalizers combined with an iterative estimation and cancelation of nonlinear distortion effects, with relatively low complexity since they allow FFT-based (Fast Fourier Transform), frequency-domain implementations. Our performance results show that the proposed receivers allow significant performance improvements at low and moderate SNR (Signal-to-Noise Ratio), even when strongly nonlinear transmitters are employed. The receiver for ZP MC-CDM is of special interest for systems where the duration of the channel impulse response is not a small fraction of the duration of the MC-CDM blocks, being suitable to MC-CDM systems with very large blocks (hundreds or even thousands of subcarriers), since they do not require the inversion nor the multiplication of large matrixes.